Hypocretin: a promising target for the regulation of homeostasis - Wang, Yutong; Fu, Su; Mao, Jian; Cui, Kun; Jiang, Hong (Frontiers in Neuroscience, 2025)
Hypocretin, also known as orexin, is a hypothalamic neuropeptide that regulates essential physiological processes including arousal, energy metabolism, feeding behavior, and emotional states. Through widespread projections and two G-protein-coupled receptors—HCRT-1R and HCRT-2R—the hypocretin system exerts diverse modulatory effects across the central nervous system. The role of hypocretin in maintaining wakefulness is well established, particularly in narcolepsy type 1 (NT1), where loss of hypocretin neurons leads to excessive daytime sleepiness and cataplexy. However, the mechanisms by which hypocretin stabilizes transitions between sleep stages remain incompletely understood. Additionally, while hypocretin integrates metabolic signals such as glucose, leptin, and ghrelin to promote feeding and energy expenditure, NT1 patients paradoxically experience weight gain despite reduced caloric intake—highlighting unresolved questions about hypocretin’s role in energy homeostasis. In the affective domain, preclinical studies suggest hypocretin enhances stress resilience and modulates anxiety- and depression-related behaviors. Yet, human data remain inconsistent, in part due to methodological variability and the limited availability of cerebrospinal fluid sampling to accurately assess central hypocretin function. Therapeutically, the hypocretin system is a promising target across several domains. Dual hypocretin receptor antagonists (DORAs), such as suvorexant and daridorexant, are clinically approved for insomnia. Selective HCRT-2R agonists—including TAK-861 and ALKS-2680—are in clinical trials for NT1 and show encouraging results. Additionally, HCRT-2R antagonists like seltorexant are being explored for major depressive disorder. This review will highlight the anatomical distribution, receptor mechanisms, and physiological functions of the hypocretin system. It will also focus to discuss its role in narcolepsy, metabolic regulation, and mood disorders, while addressing key challenges and open questions that must be resolved to fully harness hypocretin’s therapeutic potential.